Empowerment of Porang Sukoharjo Farmer Friends Group through Glucomannan-Based Gluten-Free Instant Noodle Training - Bovi Wira Harsanto; Rosita Dewati; Yoppi Syahrial; Banu Aji Wicaksono; Jeni Eka Rahmawati (Universitas Veteran Bangun Nusantara, 2025)
ABSTRACT Sahabat Petani Porang Sukoharjo (SPPS) is a productive partner engaged in the field of porang and its derivative products. SPPS has successfully processed porang tubers into glucomannan which has added value and potential. However, demand for glucomannan is still low, resulting in a lot of glucomannan being unsold. A community service team from Veteran Bangun Nusantara University, through the Community Partnership Empowerment (PKM) scheme, took the initiative to develop the downstream processing of glucomannan into healthy, low-gluten instant noodles. The main objective of this PKM activity is to be able to develop a derivative product of porang glucomannan in the form of healthy instant noodles. The problem aspect addressed by the community service team is the production aspect of healthy instant noodles. The solution provided is training in making healthy instant noodles, with the hope that SPPS will experience increased product diversity. The stages undertaken by the community service team include socialization and training accompanied by the application of technology and innovation. The results of the PKM activity are an increase in understanding of how to make healthy instant noodles by 80% and an increase in healthy instant noodle making skills by 40%. The resulting product is a healthy, low-gluten instant noodle. Future plans include intensive and regular mentoring for the production and marketing of healthy instant noodles. Keywords: Glucomannan, Porang tuber, Instant noodles, Training, SPPS